Dislocation avalanches are like earthquakes on the micron scale - Ispánovity, Péter Dusán; Ugi, Dávid; Péterffy, Gábor; Knapek, Michal; Kalácska, Szilvia; Tüzes, Dániel; Dankházi, Zoltán; Máthis, Kristián; Chmelík, František; Groma, István (Nature communications, 2022)
Compression experiments on micron-scale specimens and acoustic emission (AE) measurements on bulk samples revealed that the dislocation motion resembles a stick-slip process - a series of unpredictable local strain bursts with a scale-free size distribution. Here we present a unique experimental set-up, which detects weak AE waves of dislocation slip during the compression of Zn micropillars. Profound correlation is observed between the energies of deformation events and the emitted AE signals that, as we conclude, are induced by the collective dissipative motion of dislocations. The AE data also reveal a two-level structure of plastic events, which otherwise appear as a single stress drop. Hence, our experiments and simulations unravel the missing relationship between the properties of acoustic signals and the corresponding local deformation events. We further show by statistical analyses that despite fundamental differences in deformation mechanism and involved length- and time-scales, dislocation avalanches and earthquakes are essentially alike.